Acute epiglottitis in an adult. Issue 657 (July 1980) - Barman, S. N.; Bell, H.; Chazan, B. I.
Abstract : A 33-year old man developed acute epiglottitis of sudden onset which resulted in severe respiratory distress. A small endotracheal tube was passed as an emergency procedure. Respiratory arrest developed after he pulled it out 12 hr later. Subsequent progress was satisfactory following endotracheal intubation and treatment with ampicillin and hydrocortisone. Blood cultures grew Haemophilus influenzae.